Effects of cellulolytic fungi and biofertilizer doses on the growth and yield of tomato (Solanum lycopersicum L.) in alluvial soil/ Agus Suyanto, Agnes Tutik Purwani Irianti and Setiawan - Suyanto, Agus; Purwani Irianti, Agnes Tutik; Setiawan, . (Universiti Teknologi MARA, Sarawak, 2023)
The production and harvest areas of tomatoes in West Kalimantan tend to decrease. One of the cultivation techniques that is expected to increase the yield and quality of the plant is by using organic fertilizers. The study objective was to determine the effects of interactions between cellulolytic fungi and biofertilizer doses on the growth and yield of tomato (Solanum lycopersicum L.) in alluvial soils. A completely randomized design (CRD) with factorial patterns was applied in the research. The first factor which was cellulolytic fungi in biofertilizers (J) included: J0 (organic fertilizer without decomposer), J1 (organic fertilizer with Aspergillus sp.), J2 (organic fertilizer with Trichoderma spp.), and J3 (organic fertilizer with Aspergillus sp. and Trichoderma spp.). The second factor that was of biofertilizer doses (D) consisted of: D1 (25 g/polybag), D2 (50 g/polybag), D3 (75 g/polybag), and D4 (100 g/polybag). The results showed no significant difference between the cellulolytic fungi and biofertilizer doses on all observation variables (p>0.05).